Willingness of intensive care unit patients' family members to donate organs: A cross-sectional study. Issue 1 (6th January 2023) - Chen, Yu-Chun; Fang, Chiu-Shu; Tsai, Chi-Lun
Abstract : The large gap between the demand for, and the supply of organs worldwide makes promoting organ donation an important global social issue. Even after someone has signed a consent form or registered for organ donation, ethically, the hospital still requires a family member's written permission before organ donation can proceed. As a result, a family member rather than the patient makes the final decision. This study investigated the willingness of the family members of hypothetical patients in intensive care units (ICUs) suffering from an irreversible condition to sign an organ donation consent form. A cross-sectional survey was conducted among family members of ICU patients recruited from one medical center in southern Taiwan from April to October 2014, which followed the STROBE guidelines. Of 110 ICU family members, 71 (64.5%) were willing to donate the organs of hypothetical patients with irreversible conditions. Based on logistic regression, family support, attitude, and knowledge of organ donation significantly predicted 34% of the variance in willingness to sign consent. Attitude toward organ donation and behavioral knowledge of organ donation correlated significantly with a willingness to sign a consent form. This study found that family support and organ donation attitudes were important factors in predicting the willingness to sign a consent form for the organ donation of hypothetical patients. The study provides evidence that nurses and healthcare staff need to consider family support and educate families on organ donation to encourage potential donors to accept and agree to organ donation.